2023
DOI: 10.21608/msnj.2023.188704.1048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Educational Program for Pregnant Women on their Selected Postpartum and Newborn Care

Abstract: Background: Mother and newborns are incredibly susceptible during the post-natal period, which is also characterized by high rates of sickness and mortality. Knowledge of post-natal care plays a crucial role in preventing these problems.Aim of the study: to evaluate the impact of health educational program for pregnant women on their selected post-partum and newborn care. Research design: quasi-experimental research design (one group pre-test, post-test) was used to fulfill the aim of this study. Sample: A pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Awareness of PPD may improve recognition of symptoms and the potential to seek help [ 27 ]. Studies have shown that more knowledge about postpartum health was associated with fewer postpartum problems [ 28 , 29 ]. For pregnant women, midwives represent an important source of information about PPD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of PPD may improve recognition of symptoms and the potential to seek help [ 27 ]. Studies have shown that more knowledge about postpartum health was associated with fewer postpartum problems [ 28 , 29 ]. For pregnant women, midwives represent an important source of information about PPD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%